Teknis Pengelolaan Pembenihan Ikan Mas Mantap Cyprinus carpio untuk Mendapatkan Benih Kualitas Unggul - Iskandar, Andri; Fataya, Salsabilla Galby; Carman, Odang; Ayuningtias, Astri; Juanda, Tatang; Hidayat, Rahmat (Politeknik Negeri Sambas, 2023)
The development of mirror carp (Cyprinus carpio) farming in Indonesia has progressed very rapidly, as can be seen by the increasing number of varieties of mirror carp produced from various regions with their respective specifications and advantages. Along with the need for carp that are more resistant to environmental changes and disease attacks, the development of the Majalaya carp variety subsequently produces Mantap carp fish that are disease-resistant, and growth in the growth segment is faster. The aim of this study was to disseminate technical information on Mantap fish carp culture to the public so that it can be used as a reference source for the community, especially for cultivators who are interested in developing this fish. In this study, primary and secondary data were collected. Based on the results of a fecundity study, one female broodstock produced 104.496 kg broodstock-1, the average percentage of egg fertilization (FR) was 89,64%, the average hatching rate (HR) was 61,37%, and the average survival rate (SR) until the size of the seed size 2-3 cm reaches 60%.